Agricultural bias in focus - Balino, Sofia; Laborde Debucquet, David; Murphy, Sophia; Parent, Marie; Smaller, Carin; Traoré, Fousseini (International Institute for Sustainable Development, 2019)
The report Transforming Agriculture in Africa and Asia: What Are the Policy Priorities? showed that successful agricultural transformation has depended on interacting agricultural policies as well as the broader economic policy environment. A key finding was that agricultural transformation succeeded when governments removed the policies and addressed the market failures that disadvantaged the agricultural sector relative to the rest of the economy. We referred to this relative disadvantage as the anti-agricultural bias. To explain how these policies interact and which policies affect different aspects of the overall economy, we developed a policy taxonomy, with a focus on those that affect prices in agricultural markets (see A Policy Taxonomy for Agricultural Transformation). The policy taxonomy came from an inventory of policies collected from over 250 articles and is derived from the policy framework used in Transforming Agriculture in Africa and Asia: What Are the Policy Priorities?